Analisis Penerapan Akuntansi Zakat, Infaq dan Shadaqah (ZIS) Berdasarkan PSAK 109 Pada Badan Amil Zakat di Indonesia - Yunia Nur Azizah; Sindhi Retno Palupi; Samsul Bahri; Binti Nur Asiyah (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2022)
This research aims to find out the extent of the application of zakat and infaq / shadaqah accounting in accordance with PSAK 109 at the National Zakat Amil Agency in Indonesia. The existence of zakat can minimize the problem of poverty and create a distribution of social balance. Unlike zakat, infaq / shadaqah is not an obligation but sunnah or can be said to be voluntary. This type of research is qualitative research with literature study methods, where data sources are obtained through the collection of library data, the internet, and so on. It can be known from the results of this research that zakat and infaq / shadaqah management in BAZNAS in accordance with PSAK 109. Starting from the receipt to the distribution of zakat and infaq / shadaqah has been done very well and on target. The recording of all activities is carried out in accordance with PSAK 109 which consists of statements of financial position, statements of changes in funds, reports of changes in assets under management, statements of cash flows, and records on financial statements.